SIMBOL-SIMBOL DALAM TRADISI PERKAWINAN SKOTLANDIA DAN PAMONA SULAWESI TENGAH: SUATU ANALISIS SEMIOTIK - Sumo, Ruth Noviana; Kodong, Fentje; Lotulung, Donald R. (JURNAL ELEKTRONIK FAKULTAS SASTRA UNIVERSITAS SAM RATULANGI, 2020)
ABSTRACTThis research entitled â€œThe Traditional Symbols of Marriage in Scotland and Pamona Central Sulawesi: A Semiotic Analysisâ€. The objectives of this research are to identify, classify, describe, analyze, and contrast the kinds and meanings of the traditional symbols of marriage in Scotland and Pamona. In this research, the writer uses descriptive method. The data of traditional symbols of marriage in Scotland were collectedÂ  from several sources in the internet, while the data of traditional symbols of marriage in Pamona were collected from wedding event and by interviewing the informants to get explanations about the symbols. The writer uses Peirceâ€™s theory in anylizing the data and Ladoâ€™s theory in contrasting both symbols to find out their differences and similarities. The result of this research shows that traditional symbols of marriage in Skotland are founded ten kinds such as wedding ring, wedding dress, wedding cake, wedding kiss, luckenboot brooch, wedding bouquet, toss the brideâ€™s bouquet, quaich Skotland, ceilidh dance and honeymoon while traditional symbols of marriage in Pamona are founded four kinds such as wedding dress, necklace, sampapitu and wata oli (dowry), and dero dance. The similarities of both cultures are symbols of engagement such as ring, necklace and traditional dance. The differences of both cultures are Scotland traditional marriage has wedding cake, wedding kiss, wedding dress, luckenbooth brooch, wedding bouquet, toss the brideâ€™s bouquet, quaich Scotland, honeymoon, while in Pamona hasnâ€™t. Pamona traditionl marriage uses the symbol ofÂ  sampapitu and wata oli (dowry, while Scotland hasnâ€™t. Â Keywords: Traditional Symbols, Marriage, Scotland and Pamona, Semiotic Analysis.